Dehalococcoides as a Potential Biomarker Evidence for Uncharacterized Organohalides in Environmental Samples - Lu, Qihong; Yu, Ling; Liang, Zhiwei; Yan, Qingyun; He, Zhili; Luan, Tiangang; Liang, Dawei; Wang, Shanquan (Frontiers in Microbiology, 2017)
The massive production and improper disposal of organohalides resulted in worldwide contamination in soil and water. However, their environmental survey based on chromatographic methods was hindered by challenges in testing the extremely wide variety of organohalides. Dehalococcoides as obligate organohalide-respiring bacteria exclusively use orgnaohalides as electron acceptors to support their growth, of which the presence could be coupled with organohalides and, therefore, could be employed as a biomarker of the organohalide pollution. In this study, Dehalococcoides was screened in various samples of bioreactors and subsurface environments, showing the wide distribution of Dehalococcoides in sludge and sediment. Further laboratory cultivation confirmed the dechlorination activities of those Dehalococcoides. Among those samples, Dehalococcoides accounting for 1.8% of the total microbial community was found in an anaerobic granular sludge sample collected from a full-scale bioreactor treating petroleum wastewater. Experimental evidence suggested that the influent wastewater in the bioreactor contained bromomethane which support the growth of Dehalococcoides. This study demonstrated that Dehalococcoides could be employed as a promising biomarker to test the present of organohalides in wastestreams or other environmental samples.